Penambahan Krim dan Gula Aren dalam Formulasi Kopi Fermentasi dengan Tingkat Sangrai Berbeda - Nairul Ulfa Putri Ahmy; Budi Santoso; Agus Wijaya; Gatot Priyanto (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Ahmy NUP, Santoso B, Wijaya A, Priyanto G. 2022. Addition of cream and palm sugar in fermented coffee formulation with different roasted levels. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 388-402. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Coffee with the addition of gambier makes the functional value of coffee drinks increase, but so that the taste of this functional drink is accepted by the community, in this study the addition of cream and palm sugar. The purpose of this study was to determine the effect of the type of fermented coffee and the degree of roasting on the improvement of chemical, functional and sensory properties. This research will be carried out at the Chemical, Processing and Sensory Laboratory of Agricultural Products, Department of Agricultural Technology, Faculty of Agriculture, Sriwijaya University. This study used a completely randomized non-factorial design (RALNF) with 6 formulations. The results of this study indicate that the higher the coffee roasting rate, the lower the antioxidant activity and total phenol. This is a result of heating which can accelerate the oxidation of antioxidants contained in a material including phenolic compounds. The results of the analysis also show that the higher the roasting rate, the higher the average pH value of instant coffee. This decrease in acidity value is due to the evaporation of some acids (chlorogenic acid and carboxylic acid) when the coffee is roasted. Based on sensory results that panelists tend to like the taste of coffee with a higher roasted level and a higher concentration of palm sugar. The type of fermented coffee formulation, roasted coffee level and the addition of cream and palm sugar had a significant effect on water content, antioxidant activity, total phenol, pH of the solution.